(CoFe) Se2 (at) (CoFe)-N-C nano composite material as well as preparation method and application thereof

By using a core-shell-like (CoFe)Se2@(CoFe)-N-C nanocomposite, combining porous CoFe selenide core and nitrogen-doped carbon shell, the metal-N-C site was constructed, and the electrocatalyst was solved in the oxygen evolution reaction. The problems of slow kinetics and poor durability achieve efficient electrocatalytic performance and stability.

CN119221009APending Publication Date: 2024-12-31ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310779453.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing electrocatalysts have slow kinetics and poor durability in oxygen evolution reactions. Bimetal selenide catalysts are prone to deactivate under high current density, making it difficult to take into account both catalytic activity and stability.

Method used

Using a core-shell-like (CoFe)Se2@(CoFe)-N-C nanocomposite, the metal-N-C site is constructed through the combination of porous CoFe bimetallic selenide core and nitrogen-doped carbon shell to enhance the intrinsicity of the catalyst. Activity and stability.

Benefits of technology

A low overpotential of 270mV and a Tafel slope of 47.9mV dec-1 were achieved at 10mA cm-2, which significantly improved the oxygen evolution reaction performance and stability of the electrocatalyst, and performed better than most non-precious metal and precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221009A_ABST
    Figure CN119221009A_ABST
Patent Text Reader

Abstract

The invention relates to a (CoFe) Se2 (at) (CoFe)-N-C nano composite material as well as a preparation method and application thereof. The (CoFe) Se2 (at) (CoFe)-N-C nano composite material is of a core-shell-like structure and is in a cubic box shape, a core is porous (CoFe) Se2, the porous (CoFe) Se2 serves as the core, nitrogen-doped carbon serves as a shell, and the nitrogen-doped carbon shell captures metal atoms on the edge of the (CoFe) Se2 to form a (CoFe)-N-C structure. The preparation method is simple, the yield is large, the cost is low, the OER performance is higher than that of most non-noble metal catalysts and noble metal IrO2 catalysts when the catalyst is used as an electrocatalyst, and the catalyst maintains high catalytic ability in an alkaline environment for a long time; compared with a single-active-substance catalyst, the double-active-substance catalyst provides more active sites in an electro-catalytic reaction and has excellent catalytic capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysts, and specifically relates to a (CoFe)Se2@(CoFe)-NC nanocomposite material and a preparation method and application thereof. Background Art

[0002] Electrocatalytic oxygen evolution reaction (OER) is an important electrochemical reaction involved in many energy conversion systems, such as water splitting and metal-air batteries. However, OER involves a four-electron transfer process, which leads to slow kinetics, which greatly affects the overall energy conversion efficiency. In addition, most catalysts are not stable in alkaline environments, resulting in poor durability. Many studies have shown that enhancing the intrinsic activity of catalysts by bimetallic doping or increasing the number of catalytic active sites can effectively improve the activity or reaction rate of electrocatalyst systems. It is worth noting that most methods cannot take these two strategies into account. In recent years, transition metal selenides have been widely studied because they have suitable electronic configurations and small ionization energies, showing stronger metallicity and better conductivity. Introducing multimetallic elements is an important strategy to improve the intrinsic activity of catalyst materials. Compared with single metal catalysts, bimetallic catalysts have stronger electronic interactions, which is conducive to the occurrence of OER. Although the bimetallic selenization strategy has obvious advantages in improving intrinsic activity, the active components of the catalyst are easily deactivated at high current density, resulting in a decrease in specific surface area and active site dispersion, affecting the durability of the catalyst and failing to meet practical applications. Therefore, it is necessary to improve the performance of the catalyst by rationally designing the structure and introducing more potential active sites.

[0003] Metal atoms supported on nitrogen-doped carbon (Metal-NC) catalysts have attracted increasing attention in the past few years due to their excellent electrochemical performance. The strong coupling between metal and NC, the unique unsaturated coordination environment, and the optimized OH - The adsorption / desorption energy makes the metal-NC sites considered as effective catalytic active sites. The precise construction of metal-NC has also become one of the methods to increase the number of catalytic active sites. However, there is a technical bottleneck in the accurate synthesis of favorable metal-NC sites and the subsequent organic combination with bimetallic selenides to form high-performance catalysts with high activity and multiple active sites. The existing document CN107051568 B discloses an oxygen-evolving Fe-doped CoSe2@N-CT composite catalyst with an overpotential of 330mV and a Tafel slope of 74mV dec. -1 , there are problems of overpotential and Tafel slope being too high.

[0004] In addition, the self-aggregation of catalytic nanoparticles during the reaction will inevitably lead to a decrease in specific surface area and active site dispersion, seriously affecting catalytic activity and stability. Solving the above problems is crucial for the design and preparation of catalysts. Summary of the invention

[0005] The present invention provides a (CoFe)Se2@(CoFe)-NC nanocomposite material and a preparation method and application thereof. The prepared (CoFe)Se2@(CoFe)-NC nanocomposite material has excellent oxygen evolution catalytic activity as an electrocatalyst and excellent electrochemical stability. -2 The overpotential at the electrode is 270 mV, and the Tafel slope is as low as 47.9 mV dec. -1 .

[0006] The technical solution of the present invention is achieved as follows: a (CoFe)Se2@(CoFe)-NC nanocomposite material, wherein the (CoFe)Se2@(CoFe)-NC nanocomposite material is a core-shell structure, with porous (CoFe)Se2 as the core and nitrogen-doped carbon as the shell, wherein the nitrogen-doped carbon shell captures the edge metal atoms of (CoFe)Se2 to form a (CoFe)-NC structure.

[0007] The (CoFe)Se2@(CoFe)-NC nanocomposite material is in the shape of a cubic box, and the CoFe bimetallic selenide ((CoFe)Se2) is a porous structure with a size of about 220 nanometers, and the thickness of the nitrogen-doped carbon is 25 nanometers, wherein the nitrogen-doped carbon shell captures the metal atoms at the edge of the selenide to form a metal-NC structure.

[0008] The (CoFe)Se2@(CoFe)-NC nanocomposite material of the present invention has bimetallic cations doped into selenide to enhance the intrinsic activity of the catalyst, and at the same time, the construction of metal-NC sites increases the number of catalytic active sites, thereby enabling the (CoFe)Se2@(CoFe)-NC nanocomposite material to have excellent performance in the electrocatalytic oxygen evolution reaction, and at the same time, the core-shell structure enables it to have ultra-long stability.

[0009] A method for preparing a (CoFe)Se2@(CoFe)-NC nanocomposite material comprises the following steps:

[0010] (1) dispersing a cobalt source and a reducing agent in deionized water to obtain a solution A; dispersing an iron source in deionized water to obtain a solution B, adding the solution B dropwise into the solution A, stirring the reaction, standing, and finally centrifuging, washing, and drying to obtain a bimetallic precursor;

[0011] (2) adding the bimetallic precursor described in (1) to an aqueous solution of a surfactant to obtain a mixed system; stirring the mixed system in an ice water bath, adding pyrrole monomer, stirring evenly, and then slowly adding an aqueous solution of an oxidant to react; after the reaction is completed, centrifuging, washing, and drying to obtain a polypyrrole-coated bimetallic precursor.

[0012] (3) Selenizing the polypyrrole-coated bimetallic precursor described in (2) in an inert atmosphere to obtain a (CoFe)Se2@(CoFe)-NC nanocomposite material, wherein the heating rate of the selenization reaction is 2-5°C / min, the temperature is raised to 400-450°C, and the temperature is kept at this temperature for 2-3 hours.

[0013] Furthermore, in step (1), the cobalt source is cobalt chloride hexahydrate, the iron source is potassium ferrocyanide, and the reducing agent is potassium citrate monohydrate.

[0014] Furthermore, in step (2), the surfactant is polyvinyl pyrrolidone and the oxidant is ferric chloride hexahydrate.

[0015] Furthermore, in step (1), solution A includes 1.2 mmol of a cobalt source, 2 mmol of a reducing agent and 30 mL of deionized water; solution B includes 0.8 mmol of an iron source and 30 mL of deionized water.

[0016] Furthermore, in step (2), the amount of bimetallic precursor is 0.1 g, the concentration of the aqueous solution of the surfactant is 50 mg / mL, the amount is 25 mL, the pyrrole monomer is 0.1-0.3 mL, and the concentration of the aqueous solution of the oxidant is 0.15 mol / L, and the amount is 25 mL.

[0017] Furthermore, in step (3), the amount of the polypyrrole-coated bimetallic precursor is 30 mg, and the amount of selenium powder is 100-200 mg.

[0018] Furthermore, in step (1), the stirring rate is 500 r / s, the stirring is stopped after the reaction for 30 minutes, and the standing time is 24 hours.

[0019] A (CoFe)Se2@(CoFe)-NC nanocomposite material is prepared by the method.

[0020] Application of the (CoFe)Se2@(CoFe)-NC nanocomposite material as an electrocatalyst.

[0021] Beneficial effects of the present invention:

[0022] The (CoFe)Se2@(CoFe)-NC nanocomposite material of the present invention is a core-shell structure and presents a cubic box shape. (CoFe)Se2 is the core and nitrogen-doped carbon is the shell, wherein the nitrogen-doped carbon shell captures the metal atoms at the edge of the selenide to form a (CoFe)-NC structure. (CoFe)Se2 has a good electronic structure, which enhances the intrinsic activity of the catalyst, and the porous nanostructure is conducive to the penetration of the electrolyte and the release of bubbles. The construction of the metal-NC site provides more active sites for the electrocatalytic reaction; the nitrogen-doped carbon layer confines the porous structure of the bimetallic selenide to a limited space, effectively avoiding the structural collapse of the nanoparticles during the synthesis process and the dissolution and accumulation during the reaction process, which helps to obtain good stability in long-term cycle tests. At the same time, the coating of the nitrogen-doped carbon layer also improves the conductivity of the catalytic material, which is conducive to reducing the reaction resistance and accelerating the occurrence of the catalytic reaction.

[0023] The preparation method of the present invention is simple, has high yield and low cost. When used as an electrocatalyst, the OER performance is higher than that of most non-precious metal catalysts and precious metal IrO2 catalysts. -2 The overpotential at the electrode is 270 mV, and the Tafel slope is as low as 47.9 mV dec. -1 , has excellent stability in 500 hours of chronopotentiometry test, and is also expected to achieve excellent performance in various catalytic reactions such as catalytic oxygen reduction, methanol oxidation, ethanol oxidation, and full hydrolysis reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the preparation process of (CoFe)Se2@(CoFe)-NC nanocomposite materials;

[0026] Figure 2 The morphology of (CoFe)Se2@(CoFe)-NC nanocomposite material;

[0027] Figure 3 is the X-ray photoelectron spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite;

[0028] Figure 4 Fourier transform infrared spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite;

[0029] Figure 5 Raman spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite;

[0030] Figure 6 The test curves of Example 1, Comparative Examples 1 to 3 and the oxygen evolution reaction of the noble metal IrO2 electrocatalyst;

[0031] Figure 7 The double-layer capacitance curves of Example 1, Comparative Examples 1 to 3 and the noble metal IrO2 electrocatalyst;

[0032] Figure 8 The chronopotentiometry curve of (CoFe)Se2@(CoFe)-NC for 500 hours, and the inset is the linear sweep voltammogram before and after the 500-hour chronopotentiometry test;

[0033] Fig. 9 X-ray diffraction spectra of bimetallic selenide (CoFe)Se2 prepared at different selenization temperatures. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Embodiment 1

[0036] like Figure 1 As shown, the preparation method of (CoFe)Se2@(CoFe)-NC nanocomposite material comprises the following steps:

[0037] (1) 1.2 mmol of cobalt chloride hexahydrate and 2 mmol of potassium citrate monohydrate were dissolved in 30 mL of deionized water to form solution A; 0.8 mmol of potassium ferrocyanide was dispersed in 30 mL of deionized water to form solution B; solution B was added dropwise to solution A, the magnetic stirring rate was maintained at 500 r / s, stirring was stopped after 30 minutes of reaction, and aging (standing) was performed for 24 hours. The product was washed by centrifugation with deionized water and ethanol, and the reaction was repeated 3-6 times. Then the precipitate was dried in an oven at 60°C for 12 hours to obtain purple powdered CoFe-PBA nanocubes.

[0038] (2) Take 0.1g CoFe-PBA and add it to 25mL polyvinyl pyrrolidone solution (50mg / mL), put the mixed system into an ice-water bath, and stir it magnetically for 1 hour to make it dispersed evenly (the subsequent reaction is also carried out in an ice-water bath), add 0.2mL pyrrole monomer solution to the above mixed solution, keep stirring magnetically for 10 minutes, and then slowly add 25mL ferric chloride hexahydrate solution (0.15mol / L), and react for 5 hours. The product is washed by centrifugation with deionized water and ethanol, and repeated 3-6 times, and then the precipitate is dried in an oven at 60℃ for 12 hours to obtain a bimetallic precursor CoFe-PBA@PPy sample coated with polypyrrole.

[0039] (3) Take 30 mg of CoFe-PBA@PPy sample, put it in a quartz boat, and place it at the downwind port. Weigh 150 mg of selenium powder and put it in another quartz boat, and place it at the upwind port. Heat to 400 °C with Ar, maintain for 3 hours, and heat at a rate of 5 °C / min. Cool naturally to terminate the reaction, and obtain the final product (CoFe)Se2@(CoFe)-NC nanocomposite material.

[0040] Figure 2 This is the morphology of (CoFe)Se2@(CoFe)-NC nanocomposite material. Figure 2 a is a transmission image of a single (CoFe)Se2@(CoFe)-NC particle. It can be seen that the entire nanoparticle presents a core-shell structure. The CoFe bimetallic selenide in the core is a porous structure with a size of about 220 nanometers. The outer layer is wrapped with a 25-nanometer thick amorphous nitrogen-doped carbon layer, in which the nitrogen-doped carbon shell captures the metal atoms at the edge of the selenide to form a metal-NC structure. Figure 2 b is a high-magnification transmission image showing clear bright and dark lattice fringes with a spacing of 2.58 Å, corresponding to the (111) crystal plane of CoFe bimetallic selenide. Figure 2 c is the element mapping diagram of (CoFe)Se2@(CoFe)-NC, which shows that C, N, Co, Fe, and Se are evenly distributed. (CoFe)Se2@(CoFe)-NC has the advantages of both bimetallic selenides and metal-NC. On the one hand, bimetallic selenides enhance the intrinsic activity of the catalyst, and on the other hand, the construction of metal-NC sites can provide more reaction sites for electrocatalytic reactions. At the same time, the core-shell structure can improve the stability of the catalyst during the catalytic reaction.

[0041] Figure 3 X-ray photoelectron spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite. Figure 3a is the full XPS spectrum of the (CoFe)Se2@(CoFe)-NC nanocomposite material. It can be seen that the characteristic peak of Se appears between 50eV-200eV, indicating the successful preparation of selenide. The C 1s high-resolution XPS spectrum can be divided into three peaks, namely OC=O, CN and CC / C=C; the N 1s high-resolution XPS spectrum is divided into four peaks. In addition to graphite-N, pyridine-N and pyrrole-N, metal-N appears at 400.0eV. In the Co2p and Fe 2p high-resolution XPS spectra, the corresponding metal-N peaks and metal-Se peaks can be fitted, which indicates that the elements Co and Fe have more than one coordination environment, and metal selenide and metal-NC exist at the same time. Five different peaks can be clearly identified from the Se 3d high-resolution XPS spectrum, with two main peaks at 54.9eV and 55.9eV corresponding to Se 3d. 5 / 2 and Se3d 3 / 2 , two additional peaks appeared at 53.4 eV and 58.7 eV, corresponding to Fe 3p and Co 3p, verifying the overlap of orbitals. In addition, the appearance of Se-O at 59.5 eV indicates that the sample is slightly oxidized in air.

[0042] Figure 4 Fourier transform infrared spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite. The results show that the -1 The sharp peak at 545 cm is attributed to the characteristic stretching vibration of the C≡N bond of CoFe-PBA, while the peak at 545 cm -1 and 595cm -1 The peak at 700–1700 cm is attributed to the vibration of Fe-CN-Co chemical bonds. -1 The characteristic peaks in the shaded area belong to the characteristic peaks in the polypyrrole structure. In the (CoFe)Se2@(CoFe)-NC nanocomposite, these characteristic peaks all disappeared, indicating that the high-temperature selenization reaction destroyed the organic functional groups of the CoFe-PBA metal organic framework compound and the organic polypyrrole.

[0043] Figure 5 The Raman spectrum of (CoFe)Se2@(CoFe)-NC nanocomposite is shown in Figure 2. The results show that the ratio of D peak to G peak (I D / I G =0.92) is greater than CoFe-PBA@PPy(I D / I G=0.64), which indicates that the polypyrrole structure decomposes after selenization, generates a large number of defects and transforms into nitrogen-doped carbon. The defect-rich nitrogen-doped carbon is more conducive to capturing metal atoms to form metal-NC sites.

[0044] Comparative Example 1

[0045] The preparation method of (CoFe)Se2 nanocomposite material comprises the following steps:

[0046] (1) 1.2 mmol of cobalt chloride hexahydrate and 2 mmol of potassium citrate monohydrate were dissolved in 30 mL of deionized water to form solution A; 0.8 mmol of potassium ferrocyanide was dispersed in 30 mL of deionized water to form solution B; solution B was added dropwise to solution A, the magnetic stirring rate was maintained at 500 r / s, stirring was stopped after 30 minutes of reaction, and aging (standing) was performed for 24 hours. The product was washed by centrifugation with deionized water and ethanol, and the reaction was repeated 3-6 times. Then the precipitate was dried in an oven at 60°C for 12 hours to obtain purple powdered CoFe-PBA nanocubes.

[0047] (2) Take 30 mg of CoFe-PBA sample, place it in a quartz boat, and place it at the downwind port. Weigh 150 mg of selenium powder and place it in another quartz boat, and place it at the upwind port. Heat to 400°C with Ar, maintain for 3 hours, and increase the temperature at a rate of 5°C / min. Cool naturally to terminate the reaction, and obtain the final product (CoFe)Se2 nanocomposite material.

[0048] like Fig. 9 As shown, if the selenization temperature in step (2) is lower than 400°C, some CoFe-PBA precursor will remain and bimetallic selenide cannot be completely generated. If the selenization temperature is increased to 500°C, a miscellaneous peak will appear around 2θ=33° in the X-ray diffraction spectrum, indicating that other substances are generated. At a selenization temperature of 600°C, CoFe-PBA is converted into CoFe alloy.

[0049] Comparative Example 2

[0050] Preparation method of CoSe2@Co-NC: This comparative example is basically the same as Example 1, except that potassium ferrocyanide in step (1) is replaced by potassium cobalt cyanide.

[0051] Comparative Example 3

[0052] Preparation method of FeSe2@Fe-NC: This comparative example is basically the same as Example 1, except that the cobalt chloride hexahydrate in step (1) is replaced by ferric chloride hexahydrate.

[0053] The catalytic oxygen evolution reaction of Example 1 and Comparative Examples 1 to 3 and the noble metal IrO2 electrocatalyst were tested. The noble metal IrO2 was purchased from Aladdin Biochemical Technology Co., Ltd. The test environment was based on a three-electrode system of an electrochemical workstation and was carried out in a 1M KOH solution. The test results are shown in Figure 6 As shown, all polarization curves were not iR compensated, and all potential values ​​were measured using reversible hydrogen electrode (RHE). Figure 6 a Linear scanning voltammetry technique is used. From the test results, it can be seen that (CoFe)Se2@(CoFe)-NC has a high -2 The overpotential at is about 270 mV, which is smaller than CoSe2@Co-NC (320 mV), FeSe2@Fe-NC (422 mV), (CoFe)Se2 (300 mV), and IrO2 (332 mV), indicating that the (CoFe)Se2@(CoFe)-NC nanocomposite has the best OER performance. Figure 6 b is the Tafel slope curve obtained by fitting the linear sweep voltammetry curve. As can be seen from the figure, the Tafel slope of the (CoFe)Se2@(CoFe)-NC nanocomposite material is only 47.9 mV dec. -1 , which is lower than its CoSe2@Co-NC, FeSe2@Fe-NC, (CoFe)Se2 and IrO2 comparison materials, indicating that the kinetic reaction of (CoFe)Se2@(CoFe)-NC catalyst is faster.

[0054] Figure 7 The double-layer capacitance curves of Example 1, Comparative Examples 1 to 3, and the noble metal IrO2 electrocatalyst. The electrochemically active surface area is proportional to the double-layer capacitance, and the activity of the catalyst can be evaluated. Figure 7 The double layer capacitance of (CoFe)Se2@(CoFe)-NC nanocomposite material is as high as 52.1 mF cm -2 , which is significantly higher than CoSe2@Co-NC (24.8 mF cm -2 ), FeSe2@Fe-NC (0.22 mF cm -2 ), (CoFe)Se2(7.2mF cm -2 ) and IrO2 (1.2 mF cm -2 ), which indicates that the presence of metal-NCs greatly increases the number of active sites of the catalyst.

[0055] Figure 8The figure is a 500-hour chronopotentiometry curve of (CoFe)Se2@(CoFe)-NC, and the inset is a linear sweep voltammogram before and after the 500-hour chronopotentiometry test. After 500 hours of ultra-long chronopotentiometry, the overpotential only changes slightly, indicating that the (CoFe)Se2@(CoFe)-NC nanocomposite has excellent stability.

Claims

1. A (CoFe)Se2@(CoFe)-NC nanocomposite material, characterized in that: The (CoFe)Se2@(CoFe)-NC nanocomposite material is a core-shell structure, with porous (CoFe)Se2 as the core and nitrogen-doped carbon as the shell, wherein the nitrogen-doped carbon shell captures the edge metal atoms of (CoFe)Se2 to form a (CoFe)-NC structure.

2. A method for preparing a (CoFe)Se2@(CoFe)-NC nanocomposite material, characterized in that: The following steps are involved: (1) dispersing a cobalt source and a reducing agent in deionized water to obtain a solution A; The iron source is dispersed in deionized water to obtain solution B, and solution B is added dropwise into solution A, stirred for reaction, allowed to stand, and finally centrifuged, washed, and dried to obtain a bimetallic precursor; (2) adding the bimetallic precursor described in (1) to an aqueous solution of a surfactant to obtain a mixed system; stirring the mixed system in an ice water bath, adding pyrrole monomer, continuing to stir the mixed system, and then adding an aqueous solution of an oxidant to react. After the reaction is completed, centrifuging, washing, and drying to obtain a polypyrrole-coated bimetallic precursor. (3) Selenizing the polypyrrole-coated bimetallic precursor described in (2) in an inert atmosphere to obtain a (CoFe)Se2@(CoFe)-NC nanocomposite material, wherein the heating rate of the selenization reaction is 2-5°C / min, the temperature is raised to 400-450°C, and the temperature is kept at this temperature for 2-3 hours.

3. The preparation method according to claim 2, characterized in that: In step (1), the cobalt source is cobalt chloride hexahydrate, the iron source is potassium ferrocyanide, and the reducing agent is potassium citrate monohydrate.

4. The preparation method according to claim 2, characterized in that: In step (2), the surfactant is polyvinyl pyrrolidone and the oxidant is ferric chloride hexahydrate.

5. The preparation method according to claim 2 or 3, characterized in that: In step (1), solution A includes 1.2 mmol of a cobalt source, 2 mmol of a reducing agent and 30 mL of deionized water; solution B includes 0.8 mmol of an iron source and 30 mL of deionized water.

6. The preparation method according to claim 2 or 4, characterized in that: In step (2), the amount of bimetallic precursor is 0.1 g, the concentration of the aqueous solution of surfactant is 50 mg / mL, the amount is 25 mL, the pyrrole monomer is 0.1-0.3 mL, the concentration of the aqueous solution of oxidant is 0.15 mol / L, the amount is 25 mL.

7. The preparation method according to claim 2, characterized in that: In step (3), the amount of polypyrrole-coated bimetallic precursor is 30 mg, and the amount of selenium powder is 100-200 mg.

8. The preparation method according to claim 2, characterized in that: In step (1), the stirring rate is 500 r / s, the stirring is stopped after the reaction for 30 minutes, and the standing time is 24 hours.

9. A (CoFe)Se2@(CoFe)-NC nanocomposite material prepared by the method according to any one of claims 2 to 8.

10. Use of the (CoFe)Se2@(CoFe)-NC nanocomposite material according to claim 1 or 9 as an electrocatalyst.

Citation Information

Patent Citations

  • A Fe-doped cobalt diselenide@N-CT composite catalyst for oxygen evolution, its preparation method and application

    CN107051568B